Body Contouring Art, Science, and Clinical Practice - Shiffman, Melvin A.; Di Giuseppe, Alberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
<
PART I: ANATOMY, CLASSIFICATION OF ADIPOSITIES, BODY CONTOURING -- TODAY, MESOTHERAPY -- PART II: BREAST: Inframammary Approach to Subglandular Breast Augmentation -- Mastopexy/Reduction And Augmentation Without Vertical Scar -- Breast Reduction and Mastopexy With Vaser in Male Breast Hypertrophy -- Complications -- PART III: ABDOMEN, CHEST, BUTTOCKS -- Abdominoplasty Principles -- Body Contouring of The Abdomen in an Office-Based Practice -- Circular Lipectomy With Lateral Thigh-Buttock Lift.-PART IV: EXTREMITIES -- Grading System for Simplifying Brachioplasty -- Augmentation Brachioplasty With Cohesive Silicone Gel Implants -- Long-Term Outcomes And Complications After Brachioplasy -- Concentric Short Scar Medial Thigh Lift -- Vertical Dermocrurolipectomy -- Spiral Lift of Thighs With Buttock Lift And Augmentation -- PART V: LIPOSUCTION -- PART VI: FAT TRANSFER -- PART VII: BODY CONTOURING AFTER SEVERE WEIGHT LOSS -- Classification of Contour Deformities After Massive Weight Loss -- Total Body Lift Following Extreme Weight Loss.
Keywords: Medicine; Surgery; Medicine & Public Health; Plastic Surgery; General Surgery